Crowd control: sex ratio affects sexually selected cuticular hydrocarbons in male Drosophila serrata. (3rd January 2017) - Gershman, S. N.; Rundle, H. D.
Abstract: Although it is advantageous for males to express costly sexually selected signals when females are present, they may also benefit from suppressing these signals to avoid costly interactions with rival males. Cuticular chemical profiles frequently function as insect sexual signals; however, few studies have asked whether males alter these signals in response to their social environment. In Drosophila serrata, an Australian fly, there is sexual selection for a multivariate combination of male cuticular hydrocarbons (CHCs). Here, we show that the ratio of females to males that an adult male experiences has a strong effect on his CHC expression, with female‐biased adult sex ratios eliciting greater expression of CHC profiles associated with higher male mating success. Classical models predict that male reproductive investment should be highest when there is a small but nonzero number of rivals, but we found that males expressed the most attractive combination of CHCs when there were no rivals. We found that male CHCs were highly sensitive to adult sex ratio, with males expressing higher values of CHC profiles associated with greater mating success as the ratio of females to males increased. Moreover, sex ratio has a stronger effect on male CHC expression than adult density. Finally, we explore whether sex ratio affects the variance among a group of males in their CHC expression, as might be expected if individuals respond differently to a given social environment, but find little effect. Our results reveal that subtle differences in social environment can induce plasticity in male chemical signal expression.